2008
DOI: 10.1590/s0004-282x2008000300026
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem compression syndrome caused by vertebrobasilar dolichoectasia: microvascular repositioning technique

Abstract: Vertebrobasilar dolichoectasia (VBD) is an anatomic variant that consists of enlargement and dilatation, often associated with a tortuous and elongated vessel 1 . The anomaly is probably due to a marked thinning of the internal elastica lamina and media, most likely as a consequence of prolonged systemic arterial hypertension 2 . It accounts for approximately 3 to 5% of all cerebellopontine mass lesions. A variety of clinical syndromes have been related due to pulsatile compression by the aberrant vessel: cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 23 publications
0
37
0
2
Order By: Relevance
“…The mass effect of VBD can compress the nearby brainstem and cranial nerves, leading to symptoms such as weakness, dizziness, choking on water, cranial nerve damage, neurogenic hypertension, or pseudo space-occupying lesions within cranial fossa 4, 6, 29-31.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass effect of VBD can compress the nearby brainstem and cranial nerves, leading to symptoms such as weakness, dizziness, choking on water, cranial nerve damage, neurogenic hypertension, or pseudo space-occupying lesions within cranial fossa 4, 6, 29-31.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Although sometimes the mass effect of VBD can be very serious, the brainstem can gradually tolerate compression without showing obvious clinical symptoms. Nevertheless, some minor nerve damage can be detected that has important clinical significance 29. Passero et al found that the most common subclinical manifestations are extension of the blink reflex latency and changes in motor evoked potentials in limbs.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…19 A recent report described how the surgeon pulled the ectatic vessel away from the brain stem and fixed it to the nearby dura with unabsorbable nylon. 13 Satisfactory brain stem decompression was achieved, with subsequent symptom improvement. It should be noted that VBD with brain stem compression is an uncommon condition, and thus the reported surgical techniques and benefits claimed are merely anecdotal.…”
Section: Discussionmentioning
confidence: 98%
“…13 In the surgical approach to this condition, simply inserting a prosthesis between the vessel and the brainstem is insufficient to achieve decompression, because the size and stiffness of the dilated artery makes standard microsurgery difficult. Alternative techniques have been suggested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation